Cross-cultural adaptation and psychometric properties of the Italian version of the Patient-Specific Functional Scale (PSFS) in subjects with shoulder pain - Cioeta, Matteo; Youssef, Saad; Brindisino, Fabrizio; Venturin, Davide; Pichero, Roberto; Giovannico, Giuseppe; Pournajaf, Sanaz; Goffredo, Michela; Caselli, Serena; Pellicciari, Leonardo (Disability and rehabilitation, 2025)
To cross-culturally adapt the Patient-Specific Functional Scale (PSFS) into Italian and study its classic psychometric properties in subjects with shoulder pain (SP). The PSFS was translated into Italian and administered to 109 SP subjects. Acceptability (time to administer, floor and ceiling effects), reliability (internal consistency [Cronbach's alpha], test-retest reliability [Intraclass Correlation Coefficient (ICC)], and measurement error [Standard Error of Measurement (SEM), Minimal Detectable Change, (MDC)]), were assessed. Moreover, construct validity was investigated through hypothesis testing, comparing the PSFS with the Disability of the Shoulder, Arm and Hand (DASH) scale, 36-item Short Form Health Survey (SF-36) and Numeric Pain Rating scale (NPRS). The PSFS was successfully adapted into Italian, and its acceptability was satisfied. Internal consistency was high (Cronbach's alpha = 0.925), and test-retest reliability was good (ICC = 0.866, 95% CI = 0.749-0.931). A SEM of 0.7 points and an MDC of 1.9 points were obtained. We observed moderate evidence for construct validity, with 4/6 correlations between other measures being respected. This study provided reliability and validity of the PSFS in a sample of Italian SP subjects. Future studies should assess the responsiveness of using the PSFS as an outcome measure to capture clinical changes after treatment.